Superhydrophobic eggshell for fabrication of hydrophobic barrier of paper-based analytical device for colorimetric determination of ammonium ion in water - Thangjitsirisin, Kanyapak; Seeharaj, Panpailin; Choengchan, Nathawut (My University, 2024)
This work demonstrates the first application of the superhydrophobic eggshell as an environmental-friendly material for fabricating the hydrophobic barrier of a paper-based analytical device (PAD). The eggshell surface was modified by mixing the pulverized chicken eggshell biowaste with stearic acid and a polystyrene binder to accomplish superhydrophobicity. The PAD (10 × 10 mm2) is comprised of the circular-shaped hydrophilic reservoir (Ø 5 mm). The liquid barrier was fabricated by painting both the topside and the underside of the filter paper with the dispersed superhydrophobic eggshell solution. The SEM images revealed that the microsized superhydrophobic eggshell particles absorbed onto the porous surface of the cellulose fibril. A coated surface with a water contact angle of 155.39° ± 1.02° (n = 10) on the paper substrate was achieved, and this indicated superhydrophobicity. The eggshell barrier enabled excellent water and chemical resistance. The fabricated PAD was applied for the colorimetric determination of ammonium cations (NH4+), based on the modified Berthelot reaction. Samples and chromogenic solutions were aliquoted onto the hydrophilic reservoir, with subsequent capture of the optical image of the stable, green-colored product by a smart phone under a light-controlled studio. The green color intensities were evaluated by ImageJ™ and plotted against the standard NH4+ concentrations. A wide linear calibration range 5.0 to 100 mg N/L was achieved with good linearity (r2 > 0.99). The PAD confirmed satisfied analytical recovery (Mean ± SD: 100.6 % ± 0.97, n = 11 samples) and high precision (RSD = 0.85 %: 10-PAD replicate measurements of 1.0 mg N/L). The limit of detection (3 SD of blank/slope) of 1.05 mg N/L was found sensitive enough to monitor the NH4+ contents in freshwater. The results, determined by the developed PAD and ion chromatography, showed no significant difference under the statistical paired t-test at 95 % confidence (tstat = -1.80, tcri = 2.57, n = 6 samples).
Keywords: Ammonium; PAD; Quantitative analysis; Superhydrophobic eggshell; Water